Activities of Islamic Education in Women’s Mysticism Consultations at Babussalam Langkat - Siregar, Lailan Syahfitri; Salminawati, Salminawati; Budianti, Yusnaili (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This research investigates the activities of Islamic education within the context of women’s mysticism consultation at Babussalam Langkat using a qualitative approach with a phenomenological lens. Drawing on data from observations, interviews, documentation studies, and triangulation involving Tuan Guru, Mu’allimah Thariqat Naqsyabandiyah participants, and female salik in Babussalam Langkat, the study aims to shed light on the multifaceted dynamics of this spiritual practice. Findings unveil the historical evolution of female participation activities within the Naqsyabandiyah Order of Babussalam Langkat. Activities encompass intentions, repentance, seeking forgiveness, ablution, remembrance, communication with the Mu’allimah, dream interpretation struggles, congregational prayers, spiritual focus, and inner refinement. Outcomes include inner tranquillity, proximity to Allah SWT, heightened worship enjoyment, and fostering sincerity and kindness. The outcomes contribute to an enriched comprehension of mystical practices within the socio-cultural milieu while delving into the educational implications for women in their journey toward inner peace and spiritual enlightenment.